2021
DOI: 10.1590/1984-0462/2021/39/2019312
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of the Brazilian Version of the “Quality of Life Assessment in Spina Bifida” Questionnaire for Children and Teenagers

Abstract: Objective: To assess the reliability and validity of the Quality of Life Assessment in Spina Bifida (QUALAS), children and teenager’s versions (QUALAS C and T, respectively). This is the first self-applicable quality of life assessment tool for patients under 13 years of age, which also addresses the issue of urinary and fecal incontinence. Methods: Two urologists performed the translation of both QUALAS versions. A commission produced a consensus version (Version 2), which was applied as a pilot study to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…As a last point, our study found that, despite the short length of QUALAS-C, QUALAS-T and QUALAS-A, the comprehensiveness of the items was reported as good by the study participants, which strengthens their content validity [28,36]. Our initial find-ings are also similar to other studies regarding translating and evaluating QUALAS-C, QUALAS-T and QUALAS-A, indicating that condition-specific HRQoL issues in spina bifida are conceptually equivalent in countries such as Sweden, the US, Korea, Japan and Brazil [21,24,26,27,29,33,34,57].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As a last point, our study found that, despite the short length of QUALAS-C, QUALAS-T and QUALAS-A, the comprehensiveness of the items was reported as good by the study participants, which strengthens their content validity [28,36]. Our initial find-ings are also similar to other studies regarding translating and evaluating QUALAS-C, QUALAS-T and QUALAS-A, indicating that condition-specific HRQoL issues in spina bifida are conceptually equivalent in countries such as Sweden, the US, Korea, Japan and Brazil [21,24,26,27,29,33,34,57].…”
Section: Discussionsupporting
confidence: 83%
“…These are paramount for the international standardization and pooling of data on rare diseases [32]. The QUALAS questionnaires were developed in the US and have since been translated and evaluated in Japan, Korea and Brazil [21,24,26,27,29,33,34],…”
Section: Introductionmentioning
confidence: 99%